PENGARUH KOMPENSASI FINANSIAL DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA SARASWATI DESIGN DEVISI GARMENT DI KABUPATEN GIANYAR - I Wayan Pustawan; I Made Sumartana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2019)
This study aims to determine the effect of financial compensation and work environment partially and simultaneously on the performance of employees at CV Saraswati Design Garment Division in Gianyar. Methods of data collection used were observation, interview, documentation study, and questionnaire. Respondents used were all members of the population as much as 102 respondents. Data analysis technique used is multiple linear regression analysis, t test, and F test. Based on multiple linear regression analysis obtained regression equation that is Y = 6,514 + 0,200 X1 + 0,454 X2, partially financial compensation have positive and significant influence to employee performance with thitung> ttable (2.010> 1.984). Partial work environment has a positive and significant effect on employee performance with thitung> ttabel (7,394> 1,984). Simultaneously there is a positive and significant influence between financial compensation and work environment on employee performance with Fcount> Ftable (35,874> 3,088).